1984
DOI: 10.2172/6268623
|View full text |Cite
|
Sign up to set email alerts
|

NMR imaging and spectroscopy of the mammalian central nervous system after heavy ion radiation

Abstract: CHAPTER 1.-INTRODUCTION 1.1 Purpose and scope 1 1.2 Acknowledgements 1.3 Background 1.3.1 Radiation biophysics of the CNS 1.3.2 Relationship between NMR relaxation parameters and CNS pathology CHAPTER 2.-SPIN-ECHO IMAGING WITH PROJECTION RECONSTRUCTION 2.1 Methods 2.2 Results CHAPTER 3.-2D FOURIER TRANSFORM SPIN-ECHO IMAGING 3.1 Methods 3.2 Results CHAPTER 4.-SATURATION RECOVERY IMAGING WITH PROJECTION RECONSTRUCTION 4.1 Modification of the UCB-180 spectrometer 42 for imaging 4.2 Phantom studies 50 4.3 Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

1992
1992
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
3
0
2
Order By: Relevance
“…The gadolinium enhancement at 4 months was interesting in light of our previous work [15] and previous work by Richards and Buddinger [13] , Remler et al [16] , Karger et al [17] , Altschuler et al [18] , and Mori et al [19] . Here, we showed that at the 90 CGE level there is disruption of normal brain architecture with heterogeneous enhancement.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The gadolinium enhancement at 4 months was interesting in light of our previous work [15] and previous work by Richards and Buddinger [13] , Remler et al [16] , Karger et al [17] , Altschuler et al [18] , and Mori et al [19] . Here, we showed that at the 90 CGE level there is disruption of normal brain architecture with heterogeneous enhancement.…”
Section: Discussionmentioning
confidence: 61%
“…At 4 weeks a time point when there should be tissue injury evident by T2 weighted images and gadolinium enhancement, no changes were detected on the 4.7 T in vivo MRI examination. The study from Richards and Buddinger [13] demonstrated some changes using a 4.3 T in vivo MR spectroscopic examination. In the five animals tested at 30 Gy, they found increase in lactate relative to NAA in the treated hemisphere 11.5 weeks following irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Omary et al [13] noted gadolinium enhancement at 4 weeks following a 120-Gy dose to rat brain tissue, but did not have T 2 -weighted imaging for comparison. Richards and Budinger [14] noted that Evans blue dye could be found in the brain surrounding brain tissue treated with doses of 50 Gy as early as 4 days, but more clearly at 3 months at both 30 Gy and 50 Gy. Karger et al [6] showed that there is a larger time delay to the onset of enhancement with lower doses.…”
Section: Discussionmentioning
confidence: 99%
“…Cependant, compte tenu de l'énergie, une irradiation à dose trop élevée peut induire rapidement des lésions de coagulation. L'étude des modifications précoces induites par l'irradiation d'un hémi-cerveau de rat à des doses uniques de 15 à 50 Gy (hélium, 230 MeV), réalisée en IRM et en spectroscopie RMN du proton [43], montre assez bien que les lésions décrites et les altérations de la barrière hémato-astrocytaire ne sont pas représentatives de la radionécrose cérébrale différée. Ces lésions correspondent à la nécrose de coagulation telle qu'elle a été décrite après 40 Gy, dose unique, chez le rat [25].…”
Section: Dose Unique / Dose Fractionnée Et Anesthésie Des Animauxunclassified
“…En revanche, l'étude des temps de relaxation (7^ et T 2 ) en IRM, avec et sans injection de Gd-DTPA, 10 mois après l'irradiation de cerveau de lapin (hélium 230 MeV, doses uniques 15-30 Gy), fait apparaître une plus grande définition sur des images pondérées en T 2 et révèle des microlésions sur les images pondérées en 7", [34]. De même, l'intérêt d'aborder l'étude de la dégra-dation des lipides complexes de la glie par la spectroscopie RMN du proton a été démontré par Richards et Budinger [43] dans l'hémi-cerveau de rat juvénile normal, après irradiation à dose unique de 10-50 Gy (hélium 230 MeV). Par ailleurs, ces auteurs ont observé une augmentation du signal RMN dans l'hémi-cerveau controlatéral non irradié, observation que nous avions rapportée, également en IRM, dans un modèle d'irradiation musculaire localisée chez le lapin [33].…”
Section: Imagerieunclassified